DAKWAH SUFISTIK HAMZAH FANSURI (Kajian Substantif terhadap Syair “Perahu”) - Zakaria Zakaria (Islam Futura, 2013)
Hamzah Fansuri is an archipelago Sufism figure who wrote many works. These works are in the field of mind and his message of Sufism. Perahu poem is one of his monumnetal works. It contains the teachings of philosophical Sufism. However, the concept and substance of the poem is not widely known in the public. Hamzah Fansuri in perahu poem used many symbols. The dakwa symbols used in the perahu poem is "perahu" as the symbol of Salik (a person toward Allah) by explaining the parts of "Perahu" as an allusion steps or musyÄhadah stages. The symbols are the symbols of Allah seekers, the journey symbol toward Allah. The dakwah orientation of Hamzah Fansuri is to form a perfect human who survived in the world and the hereafter by carrying the Shari'ah, preparations for life in the grave and always adhered to the monotheism sentence (la ilaha illa Allahu).